Superficial vaginal myofibroblastoma with mushroom-like appearance: A case report with colposcopic findings and literature review - Wang, Yibei; Sun, Meige; Wang, Jiao (Frontiers in Oncology, 2022)
Superficial myofibroblastoma (SMF) of the lower female genital tract is a relatively rare benign mesenchymal tumor. The diagnosis is usually challenging as it shares several similar clinicopathological features with other tumors. Herein, we present a case of a 71-year-old Chinese female patient with postmenopausal vaginal bleeding. Colposcopy imaging revealed a well-circumscribed mass in the vagina with a wide pedicle, resembling a mushroom. The patient underwent surgery, and the tumor was histologically diagnosed as SMF. To the best of our knowledge, this is the first report of colposcopic imaging of a superficial vaginal myofibroblastoma. In this case study, we review the clinicopathological features of SMF of the lower female genital tract reported in the literature to improve the understanding of the disease.